Preoperative Oral Carbohydrate Load Versus Placebo in Major Elective Abdominal Surgery (PROCY): A Randomized, Placebo-controlled, Multicenter, Phase III Trial. Issue 4 (April 2018) - Gianotti, Luca; Biffi, Roberto; Sandini, Marta; Marrelli, Daniele; Vignali, Andrea; Caccialanza, Riccardo; Viganò, Jacopo; Sabbatini, Annarita; Di Mare, Giulio; Alessiani, Mario; Antomarchi, Francesco; Valsecchi, Maria Grazia; et al.
Abstract : Objective: To explore whether preoperative oral carbohydrate( CHO) loading could achieve a reduction in the occurrence of postoperative infections. Background: Hyperglycemia may increase the risk of infection. Preoperative CHO loading can achieve postoperative glycemic control. Methods: This was a randomized, controlled, multicenter, open-label trial. Nondiabetic adult patients who were candidates for elective major abdominal operation were randomized (1:1) to a CHO (preoperative oral intake of 800 mL of water containing 100 g of CHO) or placebo group (intake of 800 mL of water). The blood glucose level was measured every 4 hours for 4 days. Insulin was administered when the blood glucose level was >180 mg/dL. The primary endpoint was the occurrence of postoperative infection. The secondary endpoint was the number of patients needing insulin. Results: From January 2011 through December 2015, 880 patients were randomly allocated to the CHO (n = 438) or placebo (n = 442) group. From each group, 331 patients were available for the analysis. Postoperative infection occurred in 16.3% (54/331) of CHO group patients and 16.0% (53/331) of placebo group patients (relative risk 1.019, 95% confidence interval 0.720–1.442, P = 1.00). Insulin was needed in 8 (2.4%) CHO group patients and 53 (16.0%) placebo group patients (relative risk 0.15, 95% confidence interval 0.07–0.31, P < 0.001). Conclusions: Oral preoperative CHO load is effective for avoiding a blood glucose level >180 mg/dL, but without affecting the risk of postoperative infectious complication. Abstract : Supplemental Digital Content is available in the text